The Tricarballylate Utilization (tcuRABC) Genes of Salmonella enterica Serovar Typhimurium LT2 - Lewis, Jeffrey A. (American Society for Microbiology, 2004)
The genes of Salmonella enterica serovar Typhimurium LT2 encoding functions needed for the utilization of tricarballylate as a carbon and energy source were identified and their locations in the chromosome were established. Three of the tricarballylate utilization (tcu) genes, tcuABC, are organized as an operon; a fourth gene, tcuR, is located immediately 5′ to the tcuABC operon. The tcuABC operon and tcuR gene share the same direction of transcription but are independently transcribed. The tcuRABC genes are missing in the Escherichia coli K-12 chromosome. The tcuR gene is proposed to encode a regulatory protein needed for the expression of tcuABC. The tcuC gene is proposed to encode an integral membrane protein whose role is to transport tricarballylate across the cell membrane. tcuC function was sufficient to allow E. coli K-12 to grow on citrate (a tricarballylate analog) but not to allow growth of this bacterium on tricarballylate. E. coli K-12 carrying a plasmid with wild-type alleles of tcuABC grew on tricarballylate, suggesting that the functions of the TcuABC proteins were the only ones unique to S. enterica needed to catabolize tricarballylate. Analyses of the predicted amino acid sequences of the TcuAB proteins suggest that TcuA is a flavoprotein, and TcuB is likely anchored to the cell membrane and probably contains one or more Fe-S centers. The TcuB protein is proposed to work in concert with TcuA to oxidize tricarballylate to cis-aconitate, which is further catabolized via the Krebs cycle. The glyoxylate shunt is not required for growth of S. enterica on tricarballylate. A model for tricarballylate catabolism in S. enterica is proposed.